Pathology of chronic ovine periodontitis - Jansen, Márcia G.S.; Borsanelli, Ana Carolina; Dutra, Iveraldo S. [UNESP]; Ubiali, Daniel G. (FapUNIFESP (SciELO), 2022)
Periodontitis is an inflammatory process of infectious origin affecting the teeth and their supporting structures, causing significant economic losses and reducing animal welfare. Bacteria in the gingival biofilm are one of the main factors in initiating inflammatory lesions. Bacteria act directly on tissues or indirectly through substances that cause tissue damage. Studies on the etiopathogenesis of periodontitis in Brazilian sheep herds are scarce. The present study aimed to characterize histologically periodontal lesions of culled sheep from the Brazilian breed, Santa Inês. Periodontal lesions, such as periodontal pockets containing plant tissue and bacteria, replacement of the periodontal ligament by connective tissue and inflammatory cells, superficial pustules, hydropic epithelial degeneration, and epithelium hyperplasia, were observed. Submucosal changes were characterized by granulation tissue, edema, swelling of the endothelial cells, bacteria, and predominantly perivascular lymphoplasmacytic inflammatory infiltrate. In the alveolar bone, osteoclastic resorption and bone apposition were observed. This study revealed subacute to chronic inflammation, alveolar bone resorption, and cortical bone apposition in ovine periodontitis. Thus, these findings can contribute to the evolution of knowledge about the etiopathogenesis of ovine periodontitis and, possibly, the development of measures to control the disease.
Patologia da periodontite crônica em ovinos
Keywords: anaerobic; histopathology; ovine; pathology; periodontal disease; periodontitis; sheep; Sheep diseases